H1N1 2009 influenza vaccine prevention: a comparison between the Italian press and the scientific recommendations (Italian Journal of Public Health, 2011)
Methods: Messages broadcasted by the press were compared with national and internationalrecommendations regarding influenza vaccine. All of the issues of the 5 best selling national newspapersand the 2 best selling general magazines were read from 15 October 2009 to 15 November 2009 in order toselect the articles that addressed influenza vaccination. The major messages extracted from these articleswere compared with the scientific literature.Results: 217 articles out of 160 newspaper issues and 7 articles out of 8 magazine issues were selected.Articles mainly focused on the vaccine target population and on health care workers reluctance to bevaccinated. Dosage, side effects, efficacy and safety were other recurrent topics. Press-reported messageswere largely consistent with the scientific literature, except for the time interval needed between H1N1 andseasonal influenza vaccine administration.Discussion: The issue of vaccination against the H1N1 pandemic influenza received broad media attentionduring the study period. The information reported was usually correct, but sometimes it failed to conveyclear messages. In particular, concern regarding potential side effects and the low uptake of vaccinationin healthcare workers appears to have been associated with the very low vaccine uptake in the generalpopulation.
Keywords: H1N1 2009 influenza; vaccine prevention; Italian press; scientific recommendations; guidelines